Aid effectiveness in education sector of Pakistan - Mumtaz Anwar Chaudhry; Sughra Aman (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2010)
The main objective of this study is to examine the effectiveness of sector-specific foreign aid given to education sector and aggregate foreign aid on the national educational outcomes of Pakistan, respectively.
Keywords: 330